Glucosinolate and Trichome Defenses in a Natural Arabidopsis lyrata Population - Clauss, M.J; Dietel, S; Schubert, G; Mitchell-Olds, T (Journal of chemical ecology, 2006)
Glucosinolates (GS) and trichomes contribute to plant resistance against insect herbivores in the model Arabidopsis thaliana. The functional and genetic characteristics of herbivore defense, however, can differ even between closely related species. In a quantitative genetic experiment with the out-crossing perennial Arabidopsis lyrata spp. petraea, we measured constitutive GS composition, trichome density, leaf thickness, and plant resistance in four different herbivore interactions. In a single population of A. lyrata, we found heritable variation for trichome density as well as GS amount and carbon side-chain elongation ratios associated with activity in methylthioalkylmalate synthase (MAM). Unexpectedly, heritabilities for indole GS in A. lyrata were high and less affected by differences in plant age and environment than aliphatic GS. We found significant heritability in plant resistance to the specialist Plutella xylostella and generalist Trichoplusia ni, but not to the specialists Pieris brassicae and Phyllotreta cruciferae. Analyses of phenotypic and genetic correlations between candidate defense traits and insect resistance suggested that A. lyrata resistance was conferred by a combination of indole GS amount and trichome density, and, to a lesser extent, aliphatic GS ratios and leaf thickness. Variation in the most abundant compound, the aliphatic 3-hydroxypropyl GS, had little impact on A. lyrata herbivore resistance. The contribution of defense traits to resistance depended on the experimental herbivory context, and resistances were weakly correlated. A diversified defense strategy is likely to be important for long-lived individuals of A. lyrata that are subject to attack by many different herbivores in nature.